(untitled) (Ameghiniana, 2013)
The López de Bertodano Formation is located in the SW of Vcro. Marambio Island (Seymour Is.), Antarctica and is extended on the 3/5 parts of its surface. The sediments are generally grayish brown and the lower section of the profile is composed of clayed silts and calcareous bank, its total thickness about 200 m. Eighteen taxons of diatoms and two silicoflagellata were located in three samples of a consolidated dark gray claystone in a profile of the said formation. The study comprises the samples 2,3 and 4, and part of this material was already pointed out in the work of Palarnarczuk, S. et al. (1984). The associations are all of marine enviroment and the age is pointed out as upper Cretaceous, where the approximate limit between Campanian and Maastrichtian was achievied. Paleotemperature data indicate a Campanian of moderate waters from the abundance of species of the genera Stephanopyxis, Triceratium and Trinacria and the presence of Coscinodiscus lineatus f. fossilis in the Maastrichtian points out cold waters.